Effects of Strategic Sourcing on Cost Reduction: A Case Study of Manufacturing Companies in Bangladesh - Yasmin, Lamia (Global Journal of Purchasing and Procurement Management, 2024)
Purpose: The aim of the study was to analyze the effects of strategic sourcing on cost reduction: a case study of manufacturing companies in Bangladesh. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study on strategic sourcing's impact on cost reduction in Bangladeshi manufacturing firms demonstrated significant positive results. It showed that strategic sourcing led to notable reductions in procurement costs, enhanced supplier management, negotiation, and risk mitigation strategies. The findings underscored the importance of aligning procurement strategies with organizational goals for sustainable cost reductions and competitive advantages in the sector. Unique Contribution to Theory, Practice and Policy: Transaction cost economics (TCE), resource-based view (RBV) & contingency theory may be used to anchor future studies on analyze the effects of strategic sourcing on cost reduction: a case study of manufacturing companies in Bangladesh. Provide training and capacity-building programs for managers and procurement professionals in Bangladeshi manufacturing companies to enhance their understanding and implementation of strategic sourcing strategies. Advocate for policy reforms that support the development of a more transparent, competitive, and efficient supplier market in Bangladesh.